1989
DOI: 10.1136/oem.46.6.412
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin levels in farming: absence of symptoms despite high exposure levels.

Abstract: The endotoxin concentration in air was measured in farms where 11 farmers had experienced febrile reactions or allergic alveolitis and in a random sample of farms with 17 symptomless farmers. Samples were obtained during normal dairy farming in eight reference farms (background samples) and in all farms during the handling of material which had probably caused symptoms or disease or, in reference farms, maximal spore exposure (worst case samples). In addition, parallel samplers were used in reference farms, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 16 publications
(7 reference statements)
1
35
0
Order By: Relevance
“…End otoxins may thu s increase bronchial reactivity. Howe ver, it is not known whether endotoxins alone are responsible for the change in bronchial responsiveness caused by inhaled swine dust (28,30,32). For technical reasons, expo sure to endotoxins was not asse ssed in our study.…”
Section: Discussionmentioning
confidence: 80%
“…End otoxins may thu s increase bronchial reactivity. Howe ver, it is not known whether endotoxins alone are responsible for the change in bronchial responsiveness caused by inhaled swine dust (28,30,32). For technical reasons, expo sure to endotoxins was not asse ssed in our study.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, our previous exposure-response studies have shown that inhaled grain dust and endotoxin produce similar physiologic and biologic effects in humans (47,52,53) and mice (53)(54)(55)(56); the and contraction of smooth muscle (62). However, the concentration of endotoxin in the bioaerosol is not always predictive of respiratory symptoms among agricultural workers (63,64). These studies suggest that other components may be important in the development of organic dust-induced airway disease.…”
Section: Scope Of the Problemmentioning
confidence: 76%
“…(1,2,6,7,12,14,15) Occupational exposure to endotoxin occurs in a variety of industries including agriculture, wastewater plants, refuse-derived fuel production, metals machining, snowmaking, and in the manufacture of pharmaceuticals and medical devices. (3,11,12,14,18,(19)(20)(21)(22)(23)(24) Although occupational exposure limits have been suggested for endotoxin, evaluation of dose-response relationships is problematic, because sampling and analytical methods have not been standardized.…”
mentioning
confidence: 99%